A systematic review of the health effects of Acacia , Eucalyptus , and Pinus wood dust: Implications for South African occupational exposure limits - Engelbrecht, Ilzé; Horn, Suranie R.; du Plessis, Johan L. (Journal of occupational and environmental hygiene, 2025)
South Africa's commercially planted timber is mainly from the non-native genera (acacia), (eucalyptus), and (pine). These trees are popular because they are fast-growing, stress-tolerant, and commercially profitable. During timber processing, woodworkers can be exposed to wood dust through inhalation or dermal contact. Occupational exposure limits (OELs) have been developed to help protect workers against adverse health effects from overexposure to wood dust. In South Africa, the Regulations for Hazardous Chemical Agents of 2021 (RHCA 2021) list an inhalable OEL-maximum limit (ML) for wood dust from oak, beech, birch, mahogany, teak, and walnut (2 mg/m ), and OEL-restricted limit (RL) for all other species (5 mg/m ), but do not refer to acacia, eucalyptus, or pine. Due to their popularity as commercial plantation timber, these tree types may pose occupational health risks to South African woodworkers. This systematic review investigates the health effects associated with occupational exposure to acacia, eucalyptus, and pine wood dust and discusses the implications for South African OELs. A systematic literature search was conducted using EBSCO Academic Search Complete, PubMed Central, ScienceDirect, Scopus, and Web of Science. Overall, 67 articles were included in the study. The prevalence of skin and respiratory sensitization in exposed workers was <10%. Adverse dermal effects included non-allergic skin sensitivity, allergic contact dermatitis, palpable erythema, and pigmentation loss. Respiratory effects included allergic alveolitis, vocal cord dysfunction, airway inflammatory reactions, higher prevalence of respiratory symptoms, and occupational asthma. Carcinogenicity was not reported. Exposure concentrations exceeded current South African (5 mg/m , all species) and international inhalable wood dust OELs. Based on case reports, epidemiological and toxicological data, exposure studies, and current regulations, the authors propose an inhalable 8-hr time-weighted average-OEL-ML of 2 mg/m with dermal and respiratory sensitization notations for acacia, eucalyptus, and pine wood dust. To date, only has been investigated as an occupational health hazard. To create representative OELs for occupational wood dust exposure, occupational epidemiological and toxicological studies for other common timbers should be undertaken.